Only the people can save the people : constituent power, revolution, and counterrevolution in Venezuela - Kingsbury, Donald V. (State University of New York Press, 2018)
"Examines the egalitarian, creative, and inclusive practice of radical democracy in contemporary Venezuela. In a global historical moment of growing mobilizations against inequality, corruption, and exclusion, Only the People Can Save the People illustrates the necessity and challenges of more egalitarian approaches to collective life from one of the most tumultuous and compelling experiments in radical democracy. Donald V. Kingsbury examines twenty-first-century Venezuelan politics from the perspective of constituent power--the egalitarian, creative, and inclusive practice of radical democracy. In the aftermath of neoliberal structural adjustment, Venezuelan politics have been increasingly reconfigured according to principles of autogestión (self-management), social movement autonomy, protagonistic and participatory democracy, and anti-capitalism. However, inherited and intensifying challenges arising from Venezuela's status as a petrostate, the class and racial divisions that define its society, and the difficulties of defining what Hugo Chávez termed "socialism for the twenty-first century" have resulted in a tumultuous process of social change. Informed by ethnography, contemporary and comparative political thought, and global political economy, Only the People Can Save the People demonstrates how constituent power is shaping collective identity, political conflict, and infrastructural space in contemporary Latin America."--Publisher description.